Interdisciplinary Research at the Intersection of CALL, NLP, and SLA: Methodological Implications From an Input Enhancement Project. (20th February 2017) - Ziegler, Nicole; Meurers, Detmar; Rebuschat, Patrick; Ruiz, Simón; Moreno‐Vega, José L.; Chinkina, Maria; Li, Wenjing; Grey, Sarah
Abstract : Despite the promise of research conducted at the intersection of computer‐assisted language learning (CALL), natural language processing, and second language acquisition, few studies have explored the potential benefits of using intelligent CALL systems to deepen our understanding of the process and products of second language (L2) learning. The strategic use of technology offers researchers novel methodological opportunities to examine how incremental changes in L2 development occur during treatment as well as how the longitudinal impacts of experimental interventions on L2 learning outcomes occur on a case‐by‐case basis. Drawing on the pilot results from a project examining the effects of automatic input enhancement on L2 learners' development, this article explores how the use of technology offers additional methodological and analytical choices for the investigation of the process and outcomes of L2 development, illustrating the opportunities to study what learners do during visually enhanced instructional activities.